Open-Eco-Innovation for SMEs with Pan-European Key Enabling Technology Centres - Faruk Civelek (Clean Technologies, 2020)
The project “key enabling technologies for clean production” (KET4CP), which is supported by the European Commission, has the aim to connect small and medium-sized enterprises (SME) and Technology Centres (TC) for cleaner, greener and more efficient production. Within this context, SMEs and TCs across Europe work together to establish an open-innovation network and to raise awareness in productivity and environmental performance. This article presents how an open European network of TCs opens its innovation process to support SMEs to become cleaner, greener and more efficient. Furthermore, this article shows how the TCs and SMEs become a part of the open-eco-innovation platform in clean production and how successful the open-eco-innovation process of different European countries is. We revealed that a pan-European open innovation process for eco-innovations with TCs for key enabling technologies (KET TCs) and Enterprise Europe Network partners (EEN) is a successful approach for SMEs that want to produce and develop cleaner products. An application example is mentioned, in which TCs from different European countries have contributed to developing a product of a SME for energy harvesting. The SME, together with the TCs, developed a generator that is installed in city-level water supply pipes and so, it is outstanding in its application. This innovative application is also described in this article.